2013
DOI: 10.1519/jsc.0b013e31828a1fe2
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate and High School Athlete Neck Strength in Neutral and Rotated Postures

Abstract: A knowledge of neck strength is important for developing conditioning protocols and for evaluating the relationship between neck strength and head and neck injury, but very few studies have examined neck strength in relationship to athletic participation. The purpose of this study was to quantify isometric neck strength in collegiate and high school athletes. We hypothesized that (a) male athletes would have significantly greater neck strength than females; (b) collegiate athletes would be significantly strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
1
27
1
4
Order By: Relevance
“…Using the raw MVC data, a 2 (direction) 3 3 (session) repeated-measures ANOVA, with a betweengroup factor of gender, revealed a significant main effect for gender F (1,18) = 27.64, p , 0.01 indicating that the males were significantly stronger than the females, justifying the normalization of the data. A 2 3 3 repeated-measures ANOVA for the normalized peak force variables revealed a significant main effect for session (F (2,38) = 6.27, p , 0.00) and direction (F (1,19) = 165.57, p , 0.00), but no significant effect for the interaction (F (2,38) = 0.17, p = 0.84). Examination of the residuals suggested that there was a distributional difference between the 2 directions and that the variance between directions was slightly larger than that between sessions, thus violating the assumptions of the ANOVA.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Using the raw MVC data, a 2 (direction) 3 3 (session) repeated-measures ANOVA, with a betweengroup factor of gender, revealed a significant main effect for gender F (1,18) = 27.64, p , 0.01 indicating that the males were significantly stronger than the females, justifying the normalization of the data. A 2 3 3 repeated-measures ANOVA for the normalized peak force variables revealed a significant main effect for session (F (2,38) = 6.27, p , 0.00) and direction (F (1,19) = 165.57, p , 0.00), but no significant effect for the interaction (F (2,38) = 0.17, p = 0.84). Examination of the residuals suggested that there was a distributional difference between the 2 directions and that the variance between directions was slightly larger than that between sessions, thus violating the assumptions of the ANOVA.…”
Section: Resultsmentioning
confidence: 96%
“…This posture is functionally relevant for collision sports where the spine is primarily loaded in an approximately horizontal position. The majority of previous research has however been conducted in a seated position with the neck in a vertical posture (19,24,27). Within our experimental cohort, the relative reliability measures over 3 separate testing sessions ranged from good to excellent (ICCs = 0.80-0.95).…”
Section: Discussionmentioning
confidence: 93%
“…Higher incidence in females [77][78][79][80][81][82][83][84][85][86][87][88][89] Female risk factors include reduced neck girth and strength relative to head size compared to males [88][89][90][91][92][93][94] Females report more symptoms postinjury and have higher rates of postconcussive syndrome [110,111] RED-S ¼ relative energy deficiency in sport; BMI ¼ body mass index; BMD ¼ bone mineral density; BSI ¼ bone stress injury; ACL ¼ anterior cruciate ligament.…”
Section: Concussionmentioning
confidence: 99%
“…Several different factors have previously been cited to contribute to this sex and gender disparity in concussion incidence. In particular, females tend to have a reduced amount of neck girth and strength relative to head size and head-neck length compared to males [88][89][90][91][92][93][94]. This may reduce the overall stability and stiffness of the head-neck segment such that it is less able to absorb externally applied forces.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In most studies, the force was applied or measured at the forehead for flexion, at the opisthocranion for extension, and at the temple for lateral bending. There is a large variation in the strength data from literature and only (1922) presented data for both males and females. Male flexor strength, for example, ranges from 72 to 197 N and female flexor strength from 41 to 91 N. The reported strength ratios between flexion and extension range from 58% to 85% for male and 57% to 71% for female; and ratios of female to male strength range from 0.42 to 0.68 for flexion and 0.4 to 0.74 for extension.…”
Section: Methodsmentioning
confidence: 98%